Aspek Bisnis Usaha Toko Roti di Jakarta - Brastoro (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2020)
CrocoBread is a company engaged in the field of bakery, which is planned to use in a bazaar concept. CrocoBread planned to be established in Sunter Hijau Raya Blok E2/21, Sunter, North Jakarta. The intended target market is people from middle social class that likes to hang out in the mall, and lives around Jakarta area. The initial investment required by CrocoBread is IDR 200.000.000,-. this capital provided from private funding by the parents of the CrocoBread owner. The capital will be allocated to rent, purchase of the equipment, supplies, raw materials, and cash. CrocoBread will hire 5 employee in carrying out operations consisting of a manager, 2 chefs, 1 operational assistant, and 1 sales marketing. The assessment of CrocoBread performance has been assessed financially through income statement performance, cash flow projection, and balance sheet performance. Moreover, the feasibility studies of CrocoBread was done by using several methods of investment appraisal, such as: Break Even Point (BEP), Net Present Value (NPV), Payback Period (PP), and Internal Rate of Return (IRR). From those assessments and studies, the results show CrocoBread has a positive Net Present Value worth IDR 1.128.587.435,-; Break Even Point value annually less than income, Payback Period for 7 months and 17 days, and the value of Internal Rate of Return is 167%. Therefore CrocoBread is a good business to be run. Keyword: Break Even Point, Net Present Value, Payback Period, Internal Rate of Return. References: Buku Teks David, F. R., & David, F. R. (2017). Strategic Management: A Competitive Advantage Approach, Concepts and Cases, Edisi 16, Global Edition, Malaysia: Pearson Education. Saiman, L. (2014). Kewirausahaan : Teori Praktik dan Kasus-Kasus, Edisi 2, Jakarta: Salemba Empat. Kotler, P., & Armstrong, G. (2018). Principles of Marketing, Edisi 17, Global Edition, Italy: Pearson Education. Kotler, P., & Keller, K. L. (2016). Marketing Management, Edisi 15, Global Edition, United States: Pearson Education. Heizer, J., Render, B., & Munson, C. (2017). Principles of Operations Management: Sustainability and Supply Chain Management, Edisi 10, Global Edition, Malaysia: Pearson Education. Robbins, S. P., & Coulter, M. (2018). Management, Edisi 14, United States: Pearson Education. Saiman, L. (2014). Kewirausahaan : Teori Praktik dan Kasus-Kasus, Edisi 2, Jakarta: SalembaEmpat. Gitman, L. J., & Zutter, C. J. (2015). Prrinciples of Managerial Finance, Edisi 14, Global Edition, United States: Pearson Education. Weygandt,J. K,Paul, & Kieso,D (2016). Financial Accounting, Edisi 3, IFRS Edition, United States : John Wiley & Sons, Inc. Husnan, S. & Muhammad, S (2014). Studi Kelayakan Proyek Bisnis, Edisi 5, Yogyakarta: UPP STIM YKPN Ebert, R. J., & Griffin , R. W. (2017). Business Essentials, Edisi 11, Global Edition, Malaysia: Pearson Eduction. Crouhy, M., Galai, D., & Mark, R. (2014). The Essentials of Risk Management, Edisi 2, United States: Mc Graw Hill Education. Sumber Website Badan Pusat Statistik Kota Jakarta Utara (2019), Penduduk, Laju Pertumbuhan Penduduk, Distribusi Persentase Penduduk Kepadatan Penduduk, Rasio Jenis Kelamin Penduduk Menurut Kelurahan dan Kecamatan di Kota Jakarta Utara 2019, diakses pada Februari 2021, https://jakutkota.bps.go.id/indicator/12/213/1/penduduk-laju-pertumbuhan-penduduk-distribusi-persentase-penduduk-kepadatan-penduduk-rasio-jenis-kelamin-penduduk-menurut-kelurahan-dan-kecamatan-di-kota-jakarta-utara.html Bank Indonesia (2019), Kriteria UMKM, diakses pada Februari 2021, http://bi.go.id/id/tentagbi/uubi/documets/UU20Tahun2008UMKM.pdf Kemas, R (2020), Melirik Usaha Rice Box Yang Kini Sedang Berjaya, diakses pada Maret 2021, https://bisnisukm.com/melirik-usaha-rice-box-yang-kini-sedang-berjaya.html Badan Pusat Statistika (2020), Indeks Harga Konsumen dan Inflasi Bulanan Indonesia, diakses pada Februari 2021, https://www.bps.go.id/statictable/2009/06/15/907/indeks-harga-konsumen-dan-inflasi-bulanan-indonesia-2006-2020.html Badan Pusat Statistika (2020), Pendapatan per Kapita Indonesia Capai Rp 59 Juta Pada 2019, diakses pada Februari 2021, https://databoks.katadata.co.id/datapublish/2020/02/05/pendapatan-per-kapita-indonesia-capai-rp-59-juta-pada-2019 Pajak (2016), Cara Daftar NPWP Online, Online-pajak.com, diakses pada April 2021, https://www.online-pajak.com/daftar-npwp-online-wajib-pajak-orangpribadi Dinas PM & PTSP Provinsi DKI Jakarta (2021), Detail Perizinan: Surat Izin Usaha Perdagangan (SIUP) Kecil Perorangan Baru, diakses pada Juni 2021, http://pelayanan.jakarta.go.id/site/detailperizinan/571 Sandi, F, CNBC Indonesia (2020), 5 Gubernur ini Naikkan UMP 2021, Wilayah Kamu Salah Satunya?, diakses pada Juni 2021, https://www.cnbcindonesia.com/news/20201103111629-4-198878/5-gubernur-ini-naikkan-ump-2021-wilayah-kamu-salah-satunya Nabilla, F, Suara.com (2021), Rincian Tarif Listrik PLN per KWH April – Juni, diakses pada Juli 2021, https://www.suara.com/news/2021/03/11/090541/rincian-tarif-listrik-pln-per-kwh-april-juni-2021?page=all PT Aetra Air Jakarta (2021), Info Tarif Biaya Pelanggan, diakses pada Juli 2021, https://aetra.co.id/info_pelanggan/info_tarif_biaya Indihome (2021), Paket Dual Play, diakses pada Juli 2021, https://www.indihome.co.id/ Fitriya, Klikpajak.id (2021), Siapakah Yang Boleh Menggunakan Tarif PPh Final PP No 23 Tahun 2018?, diakses pada Agustus 2021, https://klikpajak.id › tarif-pph-final-pp-no-23-tahun-2018 Bank Central Asia (2020), Produk Simpanan Tahapan BCA, diakses pada Juli 2021, https://www.bca.co.id/id/Individu/Produk/Simpanan/tahapan Bank Central Asia (2020), Suku Bunga Dasar Kredit, diakses pada Agustus 2021, https://www.bca.co.id/individu/sarana/kurs-dan-suku-bunga/suku-bunga-dasar-kredit Peraturan Pemerintah dan Undang-Undang Republik Indonesia. 2008. Undang-Undang No. 20 Tahun 2008 Tentang Usaha Mikro, Kecil, dan Menengah, Lembaran Negara RI Tahun 2008, No. 93. Sekertariat Negara. Jakarta.